SYNDROMES OF BEHAVIORAL AND SPEECH DISORDERS ASSOCIATED WITH BENIGN EPILEPTIFORM DISCHARGES OF CHILDHOOD ON ELECTROENCEPHALOGRAM - I. A. Sadekov; A. V. Polyakov; I. V. Sadekova; E. A. Tupikina; V. Yu. Kochmar; T. V. Termenzhi (Русский журнал детской неврологии, 2017)
Objective: to assess the role and significance of benign epileptiform discharges of childhood (BEDC) on electroencephalogram (EEG) in development of speech and behaviorial disorders in children.Materials and methods. 90 children aged 3–7 years were included in the study: 30 of them were healthy, 30 had attention deficit hyperactivity disorder (ADHD), and 30 had expressive language disorder (ELD). We analyzed the role of persistent epileptiform activity (BEDC type) in EEG as well as frontal intermittent rhythmic delta activity in the development of some neuropsychiatric disorders and speech disorders in children.Results. We suggest to allocate a special variant of ADHD – epileptiform disintegration of behavior; we also propose the strategies for its therapeutic correction.Conclusion. Detection of epileptiform activity (BEDC type) on EEG in children with ELD is a predictor of cognitive disorders development and requires therapeutic correction, which should be aimed at stimulation of brain maturation. Detection of frontal intermittent rhythmic delta activity in children with ELD requires neurovisualization with further determining of treatment strategy.